The Planetary Health Academy - a virtual lecture series for transformative education in Germany - Gepp, Sophie; Jung, Laura; Wabnitz, Katharina; Schneider, Frederick; v Gierke, Friederike; Otto, Hannah; Hartmann, Sylvia; Gemke, Theresa; Schulz, Christian Matthias; Gabrysch, Sabine; Fast, Marischa; Schwienhorst-Stich, Eva-Maria (The lancet. Planetary health, 2023)
The planetary crises require health professionals to understand the interlinkages between health and environmental changes, and how to reduce ecological harm (ie, ecological footprint) and promote positive change (ie, ecological handprint). However, health professions’ education and training are mostly lacking these aspects. In this Viewpoint, we report findings from the evaluation of the Planetary Health Academy, the first open online lecture series for transformative planetary health education in Germany. In a retrospective online survey, 458 of 3656 Planetary Health Academy participants reported on their emotions towards climate change, attitudes towards health professionals’ responsibilities, self-efficacy, and the contribution of the Planetary Health Academy to their knowledge and actions. Additionally, motivators and barriers to acting were assessed. Our findings provide insights that can inform future efforts for transformative education. Combined with network and movement building, education could act as a social tipping element toward actions to mitigate global environmental changes.
Online verfügbar: 4. Januar 2023
Gesehen am 09.10.2023